2021
DOI: 10.1002/cncr.33589
|View full text |Cite
|
Sign up to set email alerts
|

A prospective trial of abiraterone acetate plus prednisone in Black and White men with metastatic castrate‐resistant prostate cancer

Abstract: BACKGROUND: Retrospective analyses of randomized trials suggest that Black men with metastatic castration-resistant prostate cancer (mCRPC) have longer survival than White men. The authors conducted a prospective study of abiraterone acetate plus prednisone to explore outcomes by race. METHODS: This race-stratified, multicenter study estimated radiographic progression-free survival (rPFS) in Black and White men with mCRPC. Secondary end points included prostate-specific antigen (PSA) kinetics, overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Favorable outcomes for African American men receiving abiraterone were previously observed in retrospective studies, 4,5 but no significant race-based differences in abiraterone effectiveness were found in prospective data. 6,7 It is unclear, however, whether the lack of significant differences in these prospective studies was due to insufficient power. Our study suggests that abiraterone is associated with better outcomes for African American vs non-Hispanic White men in real-world practice and extends prior analyses by investigating race-specific overall survival in a large real-world cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Favorable outcomes for African American men receiving abiraterone were previously observed in retrospective studies, 4,5 but no significant race-based differences in abiraterone effectiveness were found in prospective data. 6,7 It is unclear, however, whether the lack of significant differences in these prospective studies was due to insufficient power. Our study suggests that abiraterone is associated with better outcomes for African American vs non-Hispanic White men in real-world practice and extends prior analyses by investigating race-specific overall survival in a large real-world cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] African American patients treated with abiraterone in the Abi-Race prospective trial had longer median time to prostate-specific antigen progression than non-Hispanic White patients (16.6 vs 11.5 months, respectively) and higher rates of at least 50% prostate-specific antigen decline (74% vs 66%, respectively); however, these differences were not statistically significant. 7 It is unclear whether these outcomes extend to contemporary real-world cohorts, particularly given availability of other effective therapies, such as enzalutamide. We investigated differences in outcomes associated with first-line abiraterone between African American and non-Hispanic White men with mCRPC in a national real-world cohort, which to our knowledge represents a larger sample size with greater power than that of similar investigations to date.…”
Section: Introductionmentioning
confidence: 95%
“…In the first ever prospective multicenter study stratified by race ( NCT01940276 ), George and colleagues found that, relative to White men with mCRPC, Black men are more likely to have greater and more durable PSA responses to a combination of abiraterone acetate (Zytiga) and prednisone [ 51 ]. Abiraterone acetate is a selective, irreversible inhibitor of CYP17 and can suppress adrenal synthesis of androgen precursors as well as in situ steroidogenesis in the tumor microenvironment.…”
Section: Genetic and Molecular Basis Of Health Disparities In Prostat...mentioning
confidence: 99%
“…This increased overall survival reported in AA men occurred despite younger age, worse performance status, higher testosterone, higher PSA, and lower hemoglobin described within this population. In a prospective, multicenter study of 100 mCRPC patients treated with abiraterone acetate and prednisone entitled ABI RACE, AA patients experiences greater median PSA progression-free survival rates as well as increased rates of PSA decline ( 152 ). While adverse events were similar in all patients, fatigue was notably lower in AA men.…”
Section: The Illusion Of Inclusion In Prostate Cancer Clinical Trialsmentioning
confidence: 99%